Semi-PBPK Modeling and Simulation to Evaluate the Local and Systemic Pharmacokinetics of OC-01(Varenicline) Nasal Spray - Xiaofei Wu; Fan Zhang; Mengyang Yu; Faming Ding; Jinghui Luo; Bo Liu; Yuan Li; Zhiping Li; Hongyun Wang (Frontiers Media S.A., 2022)
This study aimed to build a nasal semi-physiologically based pharmacokinetic (PBPK) model to predict the intranasal pharmacokinetic (PK) of the OC-01(varenicline) nasal spray and accelerate the development of this drug. Based on the physiology of the human upper respiratory system, the semi-PBPK model was established and validated using systemic plasma PK data of varenicline previously observed in Americans and Chinese. Drug concentrations, both in respiratory tissue and plasma circulation system, were well simulated, and it was indicated that local concentration at the target site (nasal cavity) was significantly higher than that of plasma when OC-01 nasal spray was administered. The nasal semi-PBPK model successfully depicted the absorption and distribution of intranasal varenicline in the respiratory tissues and provided an alternative to clinical PK study of OC-01 nasal spray in Chinese. Meanwhile the current study presented a viable framework for predicting respiratory concentrations for other novel nasal spray drugs by semi-PBPK modeling.